Molecular survey and sequence analysis of Anaplasma spp. in cattle and ticks in a Malaysian farm - Tay, Sun Tee; Koh, Fui Xian; Kho, Kai Ling; Ong, Bee Lee (Malaysian Society of Parasitology and Tropical Medicine, 2014)
This study was conducted to determine the occurrence of Anaplasma spp. in the blood samples of cattle, goats, deer and ticks in a Malaysian farm. Using polymerase chain reaction (PCR) and sequencing approach, Anaplasma spp. was detected from 81(84.4%) of 96 cattle blood samples. All blood samples from 23 goats and 22 deer tested were negative. Based on the analysis of the Anaplasma partial 16S ribosomal RNA gene, four sequence types (genotypes 1 to 4) were identified in this study. Genotypes 1-3 showed high sequence similarity to those of Anaplasma platys/ Anaplasma phagocytophilum, whilst genotype 4 was identical to those of Anaplasma marginale/ Anaplasma centrale/ Anaplasma ovis. Anaplasma DNA was detected from six (5.5%) of 109 ticks which were identified as Rhipicephalus (formely known as Boophilus) microplus ticks collected from the cattle. This study reported for the first time the detection of four Anaplasma sequence types circulating in the cattle population in a farm in Malaysia. The detection of Anaplasma DNA in R. microplus ticks in this study provides evidence that the ticks are one of the potential vectors for transmission of anaplasmosis in the cattle.